Effectiveness of continuity of care in schizophrenia through virtual modality at the National Institute of Mental Health, Lima, Peru - Rosales-Gabino, Gladys L. (2026)
Objective: To determine the effectiveness of a virtual comprehensive care continuity program for individuals with paranoid schizophrenia. Methodology: A quasi-experimental design with pretest-posttest measurements was used with a sample of fifteen adults. The interdisciplinary intervention lasted six months and focused on the remote monitoring of participants. Results: Significant improvements were evidenced in treatment adherence (p = 0.018) and community skills within activities of daily living (p = 0.023). A significant decrease in positive (p = 0.016) and negative (p = 0.005) psychotic symptoms was observed, with an overall result of high relevance (p = 0.001). Regarding functionality, progress was found in cognition (p = 0.004), interpersonal relationships (p = 0.014), and social participation (p = 0.001). Although areas such as mobility, self-care, and work did not show statistically significant differences, the overall functionality score was significant (p = 0.001). Regarding family dynamics, an improvement in cohesion was recorded (p = 0.028), while adaptability did not reach statistical significance (p = 0.067). Conclusions: The program demonstrated effectiveness in key dimensions of treatment and psychosocial functioning, with positive implications for clinical management and the participants' quality of life.